2021
DOI: 10.3174/ajnr.a7168
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Utility of Disproportionately Enlarged Subarachnoid Space Hydrocephalus in Idiopathic Normal Pressure Hydrocephalus Treated with Ventriculoperitoneal Shunt Surgery: A Systematic Review and Meta-analysis

Abstract: BACKGROUND: Disproportionately enlarged subarachnoid space hydrocephalus is a specific radiologic marker for idiopathic normal pressure hydrocephalus. However, controversy exists regarding the prognostic utility of disproportionately enlarged subarachnoid space hydrocephalus. PURPOSE: Our aim was to evaluate the prevalence of disproportionately enlarged subarachnoid space hydrocephalus in idiopathic normal pressure hydrocephalus and its predictive utility regarding prognosis in patients treated with ventriculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
1
5
0
1
Order By: Relevance
“…Two systematic reviews [ 43 , 44 ] with meta-analyses have been published recently evaluating Evan’s index, callosal angle, and DESH that both performed a quantitative analysis comparing diagnostic effectiveness of these radiological markers. Both reviews found that callosal angle outperformed Evan’s index as predictor of shunt responsiveness in terms of diagnostic accuracy and intra-observer agreement.…”
Section: Introductionmentioning
confidence: 99%
“…Two systematic reviews [ 43 , 44 ] with meta-analyses have been published recently evaluating Evan’s index, callosal angle, and DESH that both performed a quantitative analysis comparing diagnostic effectiveness of these radiological markers. Both reviews found that callosal angle outperformed Evan’s index as predictor of shunt responsiveness in terms of diagnostic accuracy and intra-observer agreement.…”
Section: Introductionmentioning
confidence: 99%
“…However, the iNPH sub-population with typical imaging features is only one subgroup. The rate of detection of DESH is only approximately 30–50%, and its ability to diagnose treatment response is poor [ 12 , 16 , 27 ]. This can lead to selection bias and exclude iNPH patients with atypical imaging findings from the operation schedule.…”
Section: Discussionmentioning
confidence: 99%
“…10개의 논문을 기반으로한 메타분석에서 뇌량 각도의 정상압 수두증 진단능은 민감도 91%, 특이도 93%로 비교적 높게 보고되었다( 46 ). 하지만 다른 10개의 논문을 기반으로한 메타분석에서 DESH 소견은 특발성 정상압 수두증에서 44%에서만 보였다( 47 ). 다른 연구에서도 DESH의 민감도가 50% 미만으로 높지 않으며 일치도도 높지 않다는 한계가 지적되었다( 48 ).…”
Section: 퇴행성 뇌질환 분야에서 인공지능 적용의 미충족 수요unclassified